Behind the lens of a smartphone, Noor Azhar creates unique work - Mimi Rabita, Abdul Wahit (2023)
PEKAN, 27 January 2023 - The interest in trying something new and finding the satisfaction of working with a smartphone has inspired UMP Designer, Noor Azhar Abd. Rasid, 49, to create artwork behind his smartphone lens.